Phonkrathop khō̜ng kānčhattham paomāi tūachīwat kānphatthanā chumchon thō̜ngthin radap tambon botrīan rūppatham nai phư̄nthi Phāk Tawantok - Ratchanī Pradap (Sathāban Phatthanā ʻOngkō̜n Chumchon, 2012)
Key indicators for community development in the western region of Thailand.